2023
DOI: 10.21926/jept.2301001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotor Radius Ratio on The Performance of Hybrid Vertical Axis Wind Turbine Savonius-Darrieus NREL S809

Abstract: This research aims to know the effect of the Rotor Radius Ratio on the performance of the hybrid Vertical Axis Wind Turbine Savonius-Darrieus NREL S809 model using the Computational Fluid Dynamics method. Two-bladed Savonius is used as an internal rotor, and three-bladed Darrieus NREL S809 as an external rotor. Turbine model performance is analyzed through the value of the Moment Coefficient and Power Coefficient. The result shows that the increase in the Rotor Radius Ratio value causes an increase in the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Their study revealed that a hybrid VAWT with the Savonius above the Darrieus can generate more power than a conventional hybrid VAWT. Irawan et al 13 studied the improvements of the hybrid VAWT using the CFD approach. The 2D URANS equations were solved to obtain the complex flow problems in Ansys Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that a hybrid VAWT with the Savonius above the Darrieus can generate more power than a conventional hybrid VAWT. Irawan et al 13 studied the improvements of the hybrid VAWT using the CFD approach. The 2D URANS equations were solved to obtain the complex flow problems in Ansys Fluent.…”
Section: Introductionmentioning
confidence: 99%
“…These neural solvers combine physics with the flexibility of deep learning by building neural networks in domain knowledge. Neural solvers have been applied to solve differential equations in various fields, including computational fluid dynamics [5,6], thermodynamic prediction [7,8], rigid chemical kinetics, Eikonal equations, and so on [9][10][11]. In the modeling of mechanical dynamics, continuous time can also be modeled by neural ordinary differential equations [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this drawback, VAWTs have a lot of advantages over HAWTs [8]. As a result, from the beginning through 2022, VAWT's research continues to grow [9].…”
Section: Introductionmentioning
confidence: 99%